Spatial variability of soil greenhouse gas emissions in oil palm plantation under different management zones - Chang, Yu Yang; Sakrabani, Ruben; Golicz, Karolina K.; Kim, Sang Yoon; Tan, Ngai Paing; Sim, Choon Cheak (IOP Publishing, 2026)
As global demand for palm oil continues to rise, improving the accuracy of greenhouse gas (GHG) accounting in oil palm plantations is essential for evaluating their environmental sustainability. Spatial heterogeneity created by routine plantation management can strongly influence soil properties and GHG emissions. In this study, we assessed soil CO2, N2O, and CH4 emissions across three principal management zones in a mature oil palm (nine-year-old) plantation cultivated in mineral soils- frond heap (FH), palm circle (PC), and harvesting path (HP) under standard operational practices. Soil GHG fluxes were measured using static chambers coupled with a Fourier-transform infrared (FTIR) gas analyser, alongside surface soil (0–5 cm) sampling to characterise soil organic carbon, total nitrogen, moisture content, bulk density, porosity, and pH. In total, 90 measurement points were evaluated to capture within-plantation spatial variability. The FH zone exhibited significantly higher soil organic carbon, total nitrogen, porosity, and moisture content, and lower bulk density than the PC and HP zones. These properties translated into significant higher mean GHG fluxes in FH soils, with CO2, N2O, and CH4 emissions of 165.7 mg m−2 h−1, 0.25 mg mg m−2 h−1, and 0.25 mg m−2 h−1, respectively. In contrast, HP soils were more compacted, carbon-poor, and exhibited the lowest GHG emissions. Spearman’s rank correlation analyses indicated that CO2 emissions were primarily driven by increased soil porosity, while elevated soil moisture and organic matter inputs in FH zones promoted conditions conducive to N2O production and anaerobic microsite formation supporting CH4 emissions. When expressed as CO2-equivalents, the FH zone acted as biogeochemical hotspot, contributed disproportionately to plantation-scale GHG emissions despite occupying only one-third of the total area. These findings highlight the importance of incorporating fine-scale spatial variability when developing GHG inventories, emission factor development, and targeted, zone-specific mitigation strategies.
Keywords: greenhouse gas; soil emission; soil organic carbon; plant residue; oil palm; 41 Environmental Sciences; 4104 Environmental Management; 4106 Soil Sciences; 13 Climate Action; 37 Earth sciences; 41 Environmental sciences